Self-portrait, Family Portrait and Autofiction in Days of August (2005) of Marc Recha - Gómez Gómez, Agustín (2020)
This article analyzes the film Days of August by Marc Recha, as an autofiction work. The literary theory is taken into account, shaping the conceptual framework of this form of the self at first, and then observing how it manifests in the audio-visual range. The analysis questions the differences between audio-visual aspects of autobiography and self-portrait. The appointment of the narrator's voice in his sister’s part is particularly important in this regard. The article goes on, analyzing the articulation between the fictional and non-fictional characters, traversed by the post-memory in its link with the Spanish Civil War and landscape. Finally, an audio-visual self-portrait is constructed, which corresponds to the present while the film is produced.